Excess all-cause mortality and COVID-19-related mortality: a temporal analysis in 22 countries, from January until August 2020 - Achilleos, Souzana; Quattrocchi, Annalisa; Gabel, John; Heraclides, Alexandros; Kolokotroni, Ourania; Constantinou, Constantina; Pagola Ugarte, Maider; Nicolaou, Nicoletta; Rodriguez-Llanes, Jose Manuel; Bennett, Catherine Marie; Bogatyreva, Ekaterina; Schernhammer, Eva; et al. (My University, 2022)
This study aimed to investigate overall and sex-specific excess all-cause mortality since the inception of the COVID-19 pandemic until August 2020 among 22 countries.
Keywords: COVID-19; Infection control; Mortality; Pandemic; SARS-CoV-2